Population and food in the early twenty-first century: meeting future food demand of an increasing population - Islam, Nurul (International Food Policy Research Institute, 1995)
The product of a conference leading up to the 2020 Vision initiative, Population and Food in the Early Twenty-First Century offers technical background information on the issues of food and hunger in the coming decades. Here food, agriculture, and population experts from the World Bank, the Food and Agriculture Organization of the United Nations, IFPRI, and other organizations discuss the outlook for food demand and supply, and recommend areas of further study to help production meet the rising demand of a burgeoning world population.